Content Marketing, Brand Image, and Consumer Purchase Decisions in the Local Cosmetics Industry: Evidence from Sariayu TikTok Followers - Henny Utarsih; Diva Sri Dhamayanti (Edupedia Publisher, 2026)
Purpose – This study aims to examine the influence of Content Marketing and Brand Image on consumer Purchase Decision of Sariayu cosmetic products among TikTok followers of @sariayu_mt. The study is based on the growing role of social media marketing in the cosmetics industry, where TikTok content and brand perception may shape consumer evaluation and purchasing behavior. Methodology – This study used a quantitative method with descriptive and verificative approaches. The sample consisted of 100 respondents selected using non-probability sampling with a purposive sampling technique. Primary data were collected through questionnaires distributed to respondents who were followers of TikTok @sariayu_mt and had knowledge or purchasing experience related to Sariayu cosmetic products. The data were analyzed using validity and reliability tests, classical assumption tests, multiple linear regression, correlation analysis, coefficient of determination, and hypothesis testing through t-test and F-test with SPSS version 27. Findings – The results show that Content Marketing and Brand Image partially have a significant influence on Purchase Decision. Simultaneously, both variables also significantly influence Purchase Decision. The coefficient of determination shows that Content Marketing and Brand Image explain 86.3% of Purchase Decision, indicating that digital content and brand perception are important factors in encouraging consumers to purchase Sariayu cosmetic products. Novelty – This research contributes by examining TikTok-based content marketing and brand image in the context of a local Indonesian cosmetic brand. Significance – This study benefits cosmetic companies, digital marketers, social media managers, and future researchers in consumer behavior and digital marketing.